2014
DOI: 10.1002/cctc.201402499
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Intracrystalline Mesostructured Porosity in Zeolites by Advanced Gas Sorption, Electron Tomography and Rotation Electron Diffraction

Abstract: The Zeolite Peacemakers The cover picture shows that a new family of materials, namely mesostructured zeolites, can bridge the gap between conventional (microporous) zeolites and surfactant-templated (mesoporous) solids. In their Full Paper on p. 3110 ff., J. GarciaMartinez, X. Zou, M. Thommes and co-workers describe how size-tailored mesoporosity could be introduced into commercial zeolite Y crystals by a simple surfactant-templating post-synthetic mesostructuring process. The resulting mesoporous zeolite Y s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(153 citation statements)
references
References 33 publications
10
143
0
Order By: Relevance
“…This would suggest that the MPy þ cation is less prone to form ordered micelles after cation exchange and thus leading to a less defined porosity after calcination. These results thus strongly suggest that the described surfactant templating approach relies more on a truly zeolite rearrangement process as stipulated by the group of GarciaMartinez [40,41], and less on a dissolution-recrystallization process. Notwithstanding, further insights are necessary to determine the exact nature for the different templating behavior of these structural directing agents when used in surfactant templating of zeolites.…”
Section: Mesoporous Y Zeolite By Ionic Liquid Based Surfactant Templamentioning
confidence: 74%
See 1 more Smart Citation
“…This would suggest that the MPy þ cation is less prone to form ordered micelles after cation exchange and thus leading to a less defined porosity after calcination. These results thus strongly suggest that the described surfactant templating approach relies more on a truly zeolite rearrangement process as stipulated by the group of GarciaMartinez [40,41], and less on a dissolution-recrystallization process. Notwithstanding, further insights are necessary to determine the exact nature for the different templating behavior of these structural directing agents when used in surfactant templating of zeolites.…”
Section: Mesoporous Y Zeolite By Ionic Liquid Based Surfactant Templamentioning
confidence: 74%
“…An alternative strategy is the surfactant templating approach, which allows to impart tailored mesoporosity within given zeolite structures. Different theories exist to explain the fundamental mechanism of the surfactant templating process, that are either based on zeolite recrystallization [36e39] or rearrangement [40,41]. The recrystallization mechanism is believed to rely on a preliminary partial destruction and dissolution of the zeolite framework under basic conditions followed by the re-assembly in the presence of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…When the diffusion length decreases or the diffusion efficiency increases, reactant and product could transform quickly to and away from the acid sites within the zeolite crystals and, thus, shift the selectivity to favor the production of more valuable products at reduced yields of coke [19].…”
Section: Zsm-5 Zeolite With Special Morphologymentioning
confidence: 99%
“…Garcia-Martinez et al [19] revealed the nature of intracystalline mesopores and its connectivity by electron tomography, three-dimensional rotation electron diffraction, and high resolution gas adsorption coupled with hysteresis scanning and density functional theory. The intracystalline mesopores could act as fast channel to connect the micropores and promote the transformation of molecules, thus enhance the catalytic performance and restrain the generation of carbon deposition.…”
Section: Hierarchical Zsm-5 Zeolitementioning
confidence: 99%
“…In 2005, Garcia-Martinez et al [84][85][86][87][88] introduced a unique post-synthesis technique to make fully crystalline zeolites (i.e., Y, MOR, and ZSM-5) with well controlled mesoporosity using surfactants. The sizes of the introduced mesopores are directed by the sizes of the surfactants used, and have very narrow pore-size distributions compared to the ones obtained from a conventional desilication process.…”
Section: Surfactant-templated Zeolitesmentioning
confidence: 99%